The Effect Of Oketani Massage And Oxytoxin Massage On Breast Milk Production In Postpartum Mothers In Tpmb D In 2024 - Purnani, Weni; Darmining (Journal for Quality in Women's Health, 2025)
Breast milk is a fluid produced by the mother's breast glands since pregnancy which is the best natural food containing the best nutrition for the baby. One of the efforts to help smooth breast milk is by breast care that is carried out periodically according to procedures, namely oketani massage and oxytoxin massage so that this study aims to determine the effect of oketani massage and oxytoxin massage on breast milk production in postpartum mothers. The design of this study uses an experimental quasy with a two-group Pretest-Posttest Design. The sample size was 7 respondents in the oketani massage group, 7 respondents in the oxytocin massage group. The Wilcoxon test for Bivariate analysis and the Independent Sample T test were used to confirm the difference in breast milk production volume. The results of the study showed that Oketani massage is more effective in increasing breast milk production in postpartum mothers.